Implementasi Artificial Intelligence dalam Meningkatkan Cyber Security: Analisis ancaman dan Pencegahan - Lim Jong Su; Binastya Anggara Sekti (Ikatan Ahli Informatika Indonesia, 2024)
In today's digital age, cyber threats are becoming more complex and sophisticated.The aim of this study is to analyze the role of artificial intelligence (AI) in improving cybersecurity through threat detection and prevention. By integrating AI techniques such as machine learning and deep learning, cybersecurity systems can detect suspicious behavior patterns and identify threats in real-time.A comprehensive literature review was conducted to explore different AI approaches applied in this field, including anomaly detection analytics, threat intelligence, and automated response. The use of artificial intelligence can significantly improve the accuracy of threat detection and cyber incident response. Moreover, case studies of several organizations that have used AI for cybersecurity have shown increased effectiveness and efficiency in dealing with cyberattacks. However, there are still challenges to overcome, such as: B. Limited training data, interpretability of AI models, and the need for qualified experts. Although AI has great potential to improve cybersecurity, collaboration between technology and human expertise remains crucial to address growing threats.Thus, not only is cybersecurity improving, but there is also an increasing need to develop artificial intelligence (AI) systems that take cybersecurity threats into account in order to attack the security of information systems.